A Conserved Structural Motif Mediates Retrograde Trafficking of Shiga Toxin Types 1 and 2. (2nd November 2015) - Selyunin, Andrey S.; Mukhopadhyay, Somshuvra
Abstract : Shiga toxin‐producing Escherichia coli (STEC) produce two types of Shiga toxin (STx): STx1 and STx2. The toxin A‐subunits block protein synthesis, while the B‐subunits mediate retrograde trafficking. STEC infections do not have definitive treatments, and there is growing interest in generating toxin transport inhibitors for therapy. However, a comprehensive understanding of the mechanisms of toxin trafficking is essential for drug development. While STx2 is more toxic in vivo, prior studies focused on STx1 B‐subunit (STx1B) trafficking. Here, we show that, compared with STx1B, trafficking of the B‐subunit of STx2 (STx2B) to the Golgi occurs with slower kinetics. Despite this difference, similar to STx1B, endosome‐to‐Golgi transport of STx2B does not involve transit through degradative late endosomes and is dependent on dynamin II, epsinR, retromer and syntaxin5. Importantly, additional experiments show that a surface‐exposed loop in STx2B (β4–β5 loop) is required for its endosome‐to‐Golgi trafficking. We previously demonstrated that residues in the corresponding β4–β5 loop of STx1B are required for interaction with GPP130, the STx1B‐specific endosomal receptor, and for endosome‐to‐Golgi transport. Overall, STx1B and STx2B share a common pathway and use a similar structural motif to traffic to the Golgi, suggesting that the underlying mechanisms of endosomal sorting may be evolutionarily conserved. Abstract : Escherichia coli bacteria that produce Shiga toxin 2 (STx2) cause untreatable and life‐threatening human disease. We show that a small, surface‐exposed part of STx2 (named 'β4–β5 loop') enables the toxin to successfully intoxicate human cells. Our results imply that drugs targeting the β4–β5 loop of STx2 may be therapeutically useful.